Ancient wooden buildings as monuments of technique and technology - Wieczorek, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The most valuable monuments of the architecture and vernacular wooden buildings testify the progress of the development of building techniques during the period of time when they were created. Wooden vernacular objects which survived can be recognized as documents of fundamental professional knowledge of builders and their own innovations. During the conservation process of a wooden building we ought to recognize and protect all visible traces of old building techniques used at that time. The properties and ways of using the building materials which were usually not durable or good enough have to be taken into account nevertheless.